Caloric Expenditure of Aerobic, Resistance, or Combined High-Intensity Interval Training Using a Hydraulic Resistance System in Healthy Men. Issue 3 (March 2015) - Falcone, Paul H.; Tai, Chih-Yin; Carson, Laura R.; Joy, Jordan M.; Mosman, Matt M.; McCann, Tyler R.; Crona, Kevin P.; Kim, Michael P.; Moon, Jordan R.
Abstract : Abstract: Falcone, PH, Tai, C-Y, Carson, LR, Joy, JM, Mosman, MM, McCann, TR, Crona, KP, Kim, MP, and Moon, JR. Caloric expenditure of aerobic, resistance, or combined high-intensity interval training using a hydraulic resistance system in healthy men. J Strength Cond Res 29(3): 779–785, 2015—Although exercise regimens vary in content and duration, few studies have compared the caloric expenditure of multiple exercise modalities with the same duration. The purpose of this study was to compare the energy expenditure of single sessions of resistance, aerobic, and combined exercise with the same duration. Nine recreationally active men (age: 25 ± 7 years; height: 181.6 ± 7.6 cm; weight: 86.6 ± 7.5 kg) performed the following 4 exercises for 30 minutes: a resistance training session using 75% of their 1-repetition maximum (1RM), an endurance cycling session at 70% maximum heart rate (HRmax), an endurance treadmill session at 70% HRmax, and a high-intensity interval training (HIIT) session on a hydraulic resistance system (HRS) that included repeating intervals of 20 seconds at maximum effort followed by 40 seconds of rest. Total caloric expenditure, substrate use, heart rate (HR), and rating of perceived exertion (RPE) were recorded. Caloric expenditure was significantly ( p ⩽ 0.05) greater when exercising with the HRS (12.62 ± 2.36 kcal·min −1 ), compared with when exercising with weights (8.83 ± 1.55 kcal·min −1 ), treadmill (9.48 ± 1.30 kcal·min −1 ), and cycling (9.23 ± 1.25 kcal·min −1 ). The average HR was significantly ( p ⩽ 0.05) greater with the HRS (156 ± 9 b·min −1 ), compared with that using weights (138 ± 16 b·min −1 ), treadmill (137 ± 5 b·min −1 ), and cycle (138 ± 6 b·min −1 ). Similarly, the average RPE was significantly ( p ⩽ 0.05) higher with the HRS (16 ± 2), compared with that using weights (13 ± 2), treadmill (10 ± 2), and cycle (11 ± 1). These data suggest that individuals can burn more calories performing an HIIT session with an HRS than spending the same amount of time performing a steady-state exercise session. This form of exercise intervention may be beneficial to individuals who want to gain the benefits of both resistance and cardiovascular training but have limited time to dedicate to exercise.